Corporate Think Tanks : Zukunftsforen, Innovation Center, Design Sprints, Kreativsessions & Co. /: Zukunftsforen, Innovation Center, Design Sprints, Kreativsessions & Co. (2016) - Poguntke, Sven
No abstract available